Segmenting for sustainability: The development of a sustainability segmentation model from a Welsh sample. (March 2016) - Poortinga, Wouter; Darnton, Andrew
Abstract: Wales is one of the few countries in the world that has adopted sustainability as a central organising principle for public policy. This paper describes the development of a sustainability segmentation model that can be used to engage the public across different sustainability policy areas. A nationally representative survey (n = 1538) was conducted containing questions on the three pillars of sustainable development, human values, perceptions of climate change and energy security, and self-reported behaviours in the domains of household energy use, travel and transport, waste and recycling, and water use. A series of cluster analyses identified six segments of the public that relate differently to sustainability. Even if the segments were solely constructed on the basis of thirteen distal psycho-social indicators, they had distinct socio-demographic profiles and diverse patterns of self-reported environmental behaviour. A 15-item screening tool was developed to replicate the segments with an average 72% accuracy. Highlights: A segmentation model was developed based on people's sustainability-related beliefs. Six different publics were identified who relate to sustainability in diverse ways. The segments have distinct socio-demographic and behavioural profiles. A screening tool is essential for a segmentation model to be useful to practitioners. There are limitations to the use of audience segmentation in social marketing.